Spermidine supplementation and diffusion weighted imaging in subjective cognitive decline. (31st December 2021) - Wurdack, Katharina; Schwarz, Claudia; Benson, Gloria; Horn, Nora; Antonenko, Daria; Hofer, Sebastian; Wirth, Miranka; Sigrist, Stephan; Madeo, Frank; Flöel, Agnes
Abstract: Background: Subjective Cognitive Decline (SCD) may represent an early, pre‐clinical manifestation of Alzheimer's disease (Jessen et al., 2014), possibly accompanied by detrimental changes in white matter (WM) microstructure (Brueggen et al., 2019). Neuroprotective effects of increased external supply of spermidine were demonstrated in aged animal models (Madeo et al., 2018). This study investigated the effects of a 12‐month spermidine‐rich dietary supplementation on diffusion weighted imaging (DWI) parameters of central WM tracts in older persons with SCD. Method: The monocentre, randomised, double‐blind, placebo‐controlled phase IIb SmartAge trial (clinicaltrial.gov: NCT03094546, Wirth et al., 2019) investigates the effects of a 12‐month dietary spermidine supplementation in SCD. Baseline and follow‐up DWI data were available for 72 SCDs (mean age 69±5 years; 38 placebo, 34 spermidine). Fractional anisotropy (FA) and mean diffusivity (MD) of central WM tracts were obtained through Tract Based Spatial Statistics. The interaction effect of intervention group and time was examined through analysis of variance. Exploratory analyses of within‐group changes from baseline to follow‐up were conducted using paired t‐tests. Correction for voxelwise multiple testing was applied. Result: No statistically significant interaction effect of time and intervention group (spermidine vs. placebo) was present for FA and MD in central WM tracts. Exploratory within‐group analyses in the placebo group revealed a decrease of FA in areas comprising tracts within the limbic system and the MTL (right more than left), and an increase of FA in a small region of the right occipital lobe. Widespread increases of MD in the placebo group were observed in the right hemisphere and to a lesser extent in central regions of the left hemisphere. Within the spermidine group, no significant changes in FA or MD were present. Conclusion: While our analyses did not show an interaction effect, we found detrimental within‐group changes in FA and MD from baseline to follow‐up in the placebo group but not in the spermidine group. Our findings thus suggest a potential beneficial influence of dietary spermidine supplementation on WM microstructure in SCD, to be followed up in future larger and longer‐lasting intervention studies.